2023
DOI: 10.1186/s12889-023-16435-8
|View full text |Cite
|
Sign up to set email alerts
|

The palm or the plate? An assessment of dietary guideline promotion, awareness, and preferences among Saudis: cross-sectional survey

Aroub Alnasser

Abstract: Background Dietary Guidelines for Saudis are offered and promoted in two forms: the Healthy Food Palm and the Saudi Healthy Plate. However, public awareness, recognition, and engagement with these guidelines is not well studied. Understanding the factors behind dietary guideline promotion, awareness, recognition, and use may lead to greater optimization of and engagement with the guidelines. This study aims to assess recognition of and public engagement with the My Palm and My Plate dietary gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This could be due to a lack of awareness regarding FBDGs. Alnasser (2023) found that the majority of participants were not aware of both FBDGs outlined in the SHPDGs and the HFP; just a small percentage of participants were familiar with those guidelines by name only, while others recognized them primarily through visual illustrations [56]. It is important to note that the recognition of names and images does not necessarily correlate with the comprehension or understanding of the guidelines themselves [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to a lack of awareness regarding FBDGs. Alnasser (2023) found that the majority of participants were not aware of both FBDGs outlined in the SHPDGs and the HFP; just a small percentage of participants were familiar with those guidelines by name only, while others recognized them primarily through visual illustrations [56]. It is important to note that the recognition of names and images does not necessarily correlate with the comprehension or understanding of the guidelines themselves [56].…”
Section: Discussionmentioning
confidence: 99%
“…Alnasser (2023) found that the majority of participants were not aware of both FBDGs outlined in the SHPDGs and the HFP; just a small percentage of participants were familiar with those guidelines by name only, while others recognized them primarily through visual illustrations [56]. It is important to note that the recognition of names and images does not necessarily correlate with the comprehension or understanding of the guidelines themselves [56]. There are many barriers to a healthy diet among young adults, including unhealthy diets of family and friends, the widespread prevalence of unhealthy foods, sometimes at a relatively low cost, lack of knowledge and skills to prepare healthy foods, unhealthy snacking, stress eating, high prices of healthy foods, easy access to junk food, and, more importantly, a lack of motivation to eat healthily [28,57].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study assessing the promotion, awareness, and preferences of dietary guidelines among Saudi adults, it was reported that approximately 15% of the respondents were aware of the Saudi Healthy Eating Plate, and roughly 4.5% consumed five portions of fruits and vegetables daily. However, the study did not further investigate the relationship between awareness of the healthy eating plate and FV intake [35]. Another cross-sectional survey, along with in-depth interviews, aimed to assess the factors associated with meeting the healthy plate recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Although SA diet guidelines exist, most Saudis have unhealthy dietary habits, and the young population's consumption of refined food, meat, and sugar-sweetened beverages was high. Even more, dietary habits changed significantly during the COVID pandemic in SA; there was a 21% increase in consumption of 1 1 carbohydrates and 13% higher fat consumption, increased intake of coffee and snacks, and less consumption of fruits and vegetables [15][16][17].…”
Section: Introductionmentioning
confidence: 99%